Genetic polymorphism at RAPD loci in spring turnip rape (Brassica rapa ssp. oleifera) - Tanhuanpää, Pirjo; Vilkki, Johanna; Vilkki, Juha; Pulli, Seppo (Agricultural and Food Science, 1993)
In this study we analyzed polymorphism at RAPD loci in an outbreeding species, spring turnip rape. The reproducibility of individual RAPD patterns was high when the DNA templates were of equal quality and quantity. It was possible to use both a rapid DNA extraction method and DNA extracted from a combined sample of ten individuals without losing any of the major fragments. When different cultivars were compared for RAPD pattern, most polymorphic loci exhibited differences only in allele frequency. However, we also found fragments which were amplified only from certain cultivars. It was concluded that RAPD markers provide a fast and reliable method for analyzing individuals and cultivars of turnip rape.